Smart and gets things done : Joel Spolsky's concise guide to finding the best technical talent - Spolsky, Joel (Apress, 2007)
"In this book, Joel Spolsky reveals all his secrets - from his years at Microsoft, and as the co-founder of Fog Creek Software - for recruiting the best developers in the world." "If you've ever wondered what you should be looking for in a resume, if you've ever struggled to decide whether to hire someone at the end of an interview, or if you're wondering why you can't find great programmers, stop everything and read this book."--Jacket